Disciplining Microfinance Borrowers in Bangladesh. (September 2019) - Hussain, A. H. M. Belayeth
Based on expert interviews, this study aims to explore different components of cultural and administrative apparatuses, showing the disciplinary methods of microfinance organisations that work on submissive borrowers. Six policy officials of two microfinance institutions (MFIs) Bangladesh Rural Advancement Committee and Bangladesh Rural Development Board – and two experts from different institutions were interviewed for this purpose. Following established way of analysing expert interviews, the study concentrates on the experts' own wording and interfaces them with theoretical and conceptual positions. Among various sets of dispositif, an ensemble of elements of an apparatus, the culture of loyalty to saviours, the discourse of empowerment, regulatory decisions and policies of MFIs, a culture of repayment habits, usage of technical measures and accessing asymmetric information of borrowers are important in the power exerting process of the microfinance industry in Bangladesh.